2018
DOI: 10.1186/s12891-018-1948-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single-dose radial extracorporeal shock wave and local corticosteroid injection for treatment of carpal tunnel syndrome including mid-term efficacy: a prospective randomized controlled trial

Abstract: BackgroundRecent studies have reported that radial extracorporeal shock wave therapy (rESWT) reduces pain and improves function in patients with mild to moderately severe carpal tunnel syndrome (CTS) compared to a placebo. However, most of those studies used multi-session rESWT combined with wrist support and evaluation of efficacy was limited to a maximum of 14 weeks.MethodsThe prospective randomized controlled trial compared efficacy in relieving pain and improving clinical function between single-dose rESWT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 43 publications
(68 reference statements)
6
40
0
6
Order By: Relevance
“…Of these, 28 articles assessed patients with idiopathic CTS, 2 also assessed patients with hypertension and diabetes [ 21 , 22 ] and only 1 article assessed strictly diabetic patients [ 23 ]. Additionally, all the studies include mild and moderate severity of CTS, and 8 studies included severe CTS patients [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 28 articles assessed patients with idiopathic CTS, 2 also assessed patients with hypertension and diabetes [ 21 , 22 ] and only 1 article assessed strictly diabetic patients [ 23 ]. Additionally, all the studies include mild and moderate severity of CTS, and 8 studies included severe CTS patients [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies observed the effectiveness of drugs [ 29 , 32 , 33 , 34 , 35 , 36 ]; eight studies evaluated the effectiveness of electrotherapy [ 21 , 22 , 25 , 37 , 38 , 39 , 40 , 41 ] (diathermy, shock waves, radiofrequency, and so on); and eight studies the effect of manual therapy [ 26 , 27 , 28 , 42 , 43 , 44 , 45 , 46 ]. Three studies compared electrotherapy and a drug intervention [ 24 , 47 , 48 ] and two studies compared electrotherapy and manual therapy [ 23 , 30 ]. Two articles differed from these categories: one study analyzed the effectiveness of an alternative therapy (lavender ointment) [ 49 ] and the other one, a thermal agent (paraffin wax) [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full text articles were read, and 6 were considered relevant by qualitative analysis. [19,20,21,22,23,24] Studies selected for final inclusion (or exclusion) are shown in Figure 1, and the characteristics of the included studies are summarized in Table 1. In terms of quantitative analysis, these 6 studies (published from 2013 to 2018) fulfilled our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Ke et al [20] compared a single session ESWT of 2000 shocks to a protocol using ESWT in 3 sessions, and showed a cumulative effect of ESWT on CTS. Atthakomol et al used a single session ESWT of 5000 shocks to improve patient compliance and reported a significant effect [19] . We tried to determine the dose-response of ESWT through a meta-regression analysis.…”
Section: Discussionmentioning
confidence: 99%